An analysis of acoustic wave radiation conditions within the structural system of an axial dynamic generator - ZAMORSKI, Tomasz (Archives of Acoustics, 1987)
This paper analysis radiation conditions of an acoustic wave in an axial generator with outlets of the stator entering a common horn with a ring-shaped cross section. Acoustic properties of the generator horn, including the wave reflected from the outlet, were considered. The influence of the impedance misfit in the outlets of stater openings-horn inlet system, on the acoustic power emission was estimated. A theoretical and experimental analysis was performed in order to determine the influence of a finite horn length on the power emission and generator efficiency.